Temporal changes in plant–soil feedback effects on microbial networks, leaf metabolomics and plant–insect interactions. (24th March 2022) - Huberty, Martine; Steinauer, Katja; Heinen, Robin; Jongen, Renske; Hannula, S. Emilia; Choi, Young Hae; Bezemer, T. Martijn
Abstract: The importance of plant–soil feedbacks (PSF) for above‐ground and below‐ground multitrophic interactions is well recognized. However, most studies only condition soil for a short time before testing the feedback response. Here we investigate the influence of time of conditioning on soil microbiome composition, plant growth and metabolomics, and plant–insect interactions. We used soil collected from large outdoor mesocosms with monocultures of six species and investigated the temporal changes in the soil over a full year. Every 2 months, we assessed the legacy effects of the soils on plant growth of one of the species ( Jacobaea vulgaris ) in a climate‐controlled chamber. Each time we used tissue culture plants that were genetically identical. We also measured leaf herbivore performance and leaf metabolomes, as well as the abiotic and biotic soil properties. We show that the monoculture soils harboured different microbiomes, but that these varied over time. Growth of the test plants also varied over time and plants grew consistently less well in their own soil. The soil legacy effects on the leaf metabolome were less consistent and varied strongly over time. Networking analysis showed that soil bacteria had stronger effects on the leaf metabolome than fungi early on. However, after 12 months of conditioning, only soil fungal community composition explained the metabolomic profiles of the leaves. Insect herbivory was not affected by soil conditioning, but decreased with increasing time of conditioning. Synthesis . Our results show that the biomass response of the test plants to soil conditioning remained consistent throughout the year, even though both the soil microbiome and leaf metabolomic responses to conditioned soil varied greatly over time. These soil‐induced changes in the metabolome of plants over time can be an important driver of above‐ground multitrophic interactions in nature. Our study demonstrates that the duration of conditioning has a strong impact on plant and soil properties, which highlights that temporal variation is an important aspect to consider in future studies investigating plant–soil interactions. Abstract : Time changes everything, or not? Here, we investigate the effect of time of conditioning on soil microbiome composition, plant growth and metabolomics, and plant–insect interactions. The microbiome of the soils changes over time but its influence on plant–soil feedback patterns stays remarkably similar. However, the influence of the changing soil microbiome on the metabolome changes strongly over time.